Non-suicidal self-injury in Portuguese college students: relationship with emotion regulation, resilience and self-compassion - Gonçalves, Sónia (2023)
Non-Suicidal Self-Injury (NSSI) are behaviors relatively frequent among college students and seem to be associated to difficulties in emotion regulation. Less is known, however, about the relationship of NSSI with protective factors such as resilience and self-compassion. The aims of this study are to compare three groups of Portuguese college students (without NSSI, past NSSI, and current NSSI) regarding difficulties in emotion regulation, resilience, and self-compassion and to evaluate the predictors of NSSI considering demographics and those risk and protective factors. Three hundred and eighty-five college students were evaluated through self-report measures. Ninety participants (23.4%) reported lifetime NSSI. These participants reported higher difficulties in emotion regulation and lower resilience and self-compassion than the group without NSSI. The group with current NSSI presented the lowest levels of resilience and self-compassion. Lifetime NSSI was significantly associated with past suicide attempts. Past psychopathology and lower self-compassion were predictors of NSSI. Interventions for decrease NSSI in college students should promote adaptive emotion regulation strategies, resilience, and self-compassion.